HUMAN CAPITAL APPROACH TO DEVELOPING FINANCIAL LITERACY IN THE DIGITAL ERA - Eshpulatova Muazzam Barnoyevna, (TADQIQOTLAR, 2025)
Abstract The rapid digitalization of financial systems has fundamentally transformed the way individuals interact with financial markets, institutions, and services. While digital financial  technologies  have  increased  access  to  financial  products  and  enhanced financial  inclusion,  they  have  also  introduced  new  risks  related  to  information asymmetry, behavioral biases, and digital fraud. This extended thesis examines the development of financial literacy in the digital era through the human capital approach. It  argues  that  financial  literacy—particularly  digital  financial  literacy—should  be treated  as  a  core  component  of  human  capital  that  directly  influences  financial behavior, economic security, and sustainable development. Drawing on human capital theory,  behavioral  economics,  and  international  empirical  evidence,  the  study highlights  the  importance  of  education,  institutional  coordination,  and  digital competencies  in  strengthening  financial  literacy  and  ensuring  responsible  financial behavior in the digital age.